2018
DOI: 10.1037/xhp0000518
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in unimodal visual vowel perception: The roles of oral-facial kinematics, orientation, and configuration.

Abstract: Masapollo, Polka, and Ménard (2017) recently reported a robust directional asymmetry in unimodal visual vowel perception: Adult perceivers discriminate a change from an English /u/ viseme to a French /u/ viseme significantly better than a change in the reverse direction. This asymmetry replicates a frequent pattern found in unimodal auditory vowel perception that points to a universal bias favoring more extreme vocalic articulations, which lead to acoustic signals with increased formant convergence. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…For gestural theories, compensation for coarticulation reflects speech perception's capacity to bypass low-dimensional acoustic variability (i.e., in frequency means or intensity patterns) and to find invariant structure in gestures (Fowler, 2006 ). These gestures set up a context that shapes the perception of a target phoneme, but because gestures are themselves context-sensitive, gestural theories encompass a broad set of structures unfolding and interacting with one another across a variety of time scales, e.g., the entire phrase in which a phoneme occurs (Tilsen, 2009 ), the surrounding discourse (Skipper et al, 2017 ), the facial movements implicated in articulation (Massapollo et al, 2018 ), the social setting and concurrent multimodal sensory information (Levinson and Holler, 2014 ), the language itself (Tobin et al, 2017 ). Compared with the extremely stringent just-previous-sound definition of context from general-auditory theorists, the gestural-theoretic context risks seeming sprawling and perhaps unfalsifiably vast.…”
Section: Resultsmentioning
confidence: 99%
“…For gestural theories, compensation for coarticulation reflects speech perception's capacity to bypass low-dimensional acoustic variability (i.e., in frequency means or intensity patterns) and to find invariant structure in gestures (Fowler, 2006 ). These gestures set up a context that shapes the perception of a target phoneme, but because gestures are themselves context-sensitive, gestural theories encompass a broad set of structures unfolding and interacting with one another across a variety of time scales, e.g., the entire phrase in which a phoneme occurs (Tilsen, 2009 ), the surrounding discourse (Skipper et al, 2017 ), the facial movements implicated in articulation (Massapollo et al, 2018 ), the social setting and concurrent multimodal sensory information (Levinson and Holler, 2014 ), the language itself (Tobin et al, 2017 ). Compared with the extremely stringent just-previous-sound definition of context from general-auditory theorists, the gestural-theoretic context risks seeming sprawling and perhaps unfalsifiably vast.…”
Section: Resultsmentioning
confidence: 99%
“…By this account, the foregoing findings do not derive from basic psychoacoustic processes. Indeed, recent results have provided evidence that is compatible with this view (Polka & Bohn, 2011; Masapollo et al ., 2018; Masapollo et al ., under review). For example, Masapollo, Franklin, Morgan and Polka (under review) found that asymmetries in adult vowel perception were diminished in discrimination tasks that reduced demands on phonological working memory.…”
Section: Introductionmentioning
confidence: 63%
“…Another focus was on how factors such as phonological working memory capacity, attention, and particular task demands interact to influence asymmetries. This framework has been used to guide a number of recent studies of vowel perception with both adults and infants (see, e.g., Pons et al ., 2012; Tyler, Best, Faber, & Levitt, 2014; Kriengwatana & Escudero, 2017; Masapollo, Polka, Molnar, & Ménard, 2017a; Masapollo, Polka, & Ménard, 2017b; Masapollo, Polka, Ménard, Franklin, Tiede & Morgan, 2018; Masapollo, Franklin, Morgan & Polka, under review), which have informed our understanding of the nature of the interplay between initial discrimination abilities and biases and linguistic experience in vowel perception.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the authors argued that there is a universal bias towards more focalized vowels in adults, too. These results have been replicated and extended in that the universal bias seems to have an impact not only on the auditory domain of speech processing but also on visual vowel discrimination (Masapollo et al, 2017a , 2018 ).…”
Section: Introductionmentioning
confidence: 69%